Análisis de la calidad de absorción visual de las unidades del paisaje del páramo Llamahuasi de la comunidad de Cumbijin en la ciudad de Salcedo, propuesta de conservación, 2023. - Fonseca Acosta, Gissela Marili (2023)
The present research work was developed with the objective of establishing the quality and visual fragility of the components of the landscape units of the páramo in the Community of Cumbijin itself, located in the province of Cotopaxi. A methodology was applied focused on the characterization of landscape units, production systems based on the guidelines established by the Bureau of Land Management (BLM) method for the assessment of visual quality, visual absorption quality (CAV) and subsequently the fragility and visual sensitivity. An approach of qualitative values was established, which were identified through photographs that agreed to give value to each of the criteria and elements determined for the visual evaluation of the landscape through the analysis of the photographs recorded in the study place. To obtain the photographs, field visits were made and to arrive at the characterization of the different activities that take place in the place. According to the results, it was established that the páramo has an average visual quality of class B, where its areas whose features have variety in shape, color, line and texture, but which are common in the studied region and not exceptional, with a average of 13 points, the visual absorption capacity belongs to class II expressing the fragility of the medium landscape with an average of 31.5, therefore it is in the CAV range of 19 to 36 points, with moderate fragility. It is concluded that there is a need to implement conservation, care and landscape management activities, being essential to establish a proposal for conservation, regeneration and restoration of the area under study.